Associations of serum cystatin C concentrations with total mortality and mortality of 12 site-specific cancers - Huang, Changzhi; Lu, Jiayi; Yang, Jing; Wang, Zhenling; Hang, Dong; Fu, Zan (Frontiers in Molecular Biosciences, 2024)
Purpose: Cystatin C (CysC), beyond its biomarker role of renal function, has been implicated in various physical and pathological activities. However, it remains unknown about the impact of serum CysC on cancer mortality in a general population. To examine the associations of serum CysC concentrations and mortality of total and 12 site-specific cancers.We included 241,008 participants with CysC measurements, who had normal creatinine-based estimated glomerular filtration rates and were free of cancer and renal diseases at baseline (2006)(2007)(2008)(2009)(2010) of the UK Biobank cohort. Death information was obtained from the National Health Service death records through February 28, 2021. Multivariable Cox proportional hazards models were used to compute hazard ratios (HR) per one standard deviation increase in log-transformed CysC concentrations and 95% confidence intervals (95% CI) for mortality.Results: Over a median follow-up of 12.1 (interquartile range, 11.3-12.8) years, 5744 cancer deaths occurred. We observed a positive association between serum CysC concentrations and total cancer mortality (HR=1.16, 95% CI: 1.12-1.20). Specifically, participants with higher serum CysC concentrations had increased mortality due to lung cancer (HR=1.12, 95% CI: 1.05-1.20), blood cancer (HR=1.29, 95% CI: 1.16-1.44), brain cancer (HR=1.19, 95% CI: 1.04-1.36), esophageal cancer (HR=1.20, 95% CI: 1.05-1.37), breast cancer (HR=1.18, 95% CI:1.03-1.36), and liver cancer (HR=1.49, 95% CI: 1.31-1.69).Our findings indicate that higher CysC concentrations are associated with increased mortality due to lung, blood, brain, esophageal, breast, and liver cancers. Future studies are necessary to clarify underlying mechanisms.